Novel nickel promoted illite clay based catalyst for autothermal dry reforming of methane. (15th August 2016) - Akri, Mohcin; Chafik, Tarik; Granger, Pascal; Ayrault, Philippe; Batiot-Dupeyrat, Catherine
Graphical abstract: Highlights: Illite natural clay is an interesting support for the autothermal reforming of CH4. The addition of Ce increases the surface area and the dispersion of nickel particles. The best catalytic activity and stability are obtained with the catalyst containing 15% in weight of Ce. High CH4 and CO2 conversions are maintain during 4 h on stream in the presence of O2. Abstract: A series of Ni–Ce catalysts supported on illite clay containing different cerium loading were tested with respect to autothermal reforming of methane at 800 °C using a GHSV = 60, 000 mL g −1 h −1 . The addition of oxygen in the gaseous reactant feed, under the used experimental condition was found to play a key role since the carbon balance is significantly higher as compared to CH4 /CO2 mixture. The addition of cerium was found to enhance the specific surface area as result of meso-porosity development. Furthermore, the nickel particles become smaller in the presence of Ce, decreasing the Ni° average size from 34.2 for 10Ni to 16.3 nm for 10Ni15Ce. The best catalytic activity and stability were obtained on the catalyst containing 15 wt.% of cerium, apparently attributed to its redox properties and further improvement on the nickel dispersion. It should be pointed out that the observed catalytic performance was high even after 24 h under reaction stream.